Clinical outcomes of left bundle branch pacing compared to right ventricular apical pacing in patients with atrioventricular block. Issue 4 (11th March 2021) - Zhang, Shigeng; Guo, Junfang; Tao, Aibin; Zhang, Baowei; Bao, Zhonghua; Zhang, Guohui
Abstract: Background: Left bundle branch pacing (LBBP) can produce near normalization of QRS duration. This has recently emerged as alternative technique to right ventricular pacing and His bundle pacing. Hypothesis: The purpose of this study is to evaluate clinical outcomes of LBBP compared to right ventricular apical pacing (RVAP). Methods: A total of 70 AVB patients with indications for ventricular pacing were retrospectively studied. LBBP was attempted in 33 patients, classified as LBBP group. The other patients were classified as RVAP group. Pacing parameters, electrocardiogram and echocardiogram characteristics, heart failure hospitalization (HFH), and atrial fibrillation (AF) were evaluated perioperatively and at follow‐ups. Patients were followed in the device clinic for a minimum of 12 months and up to 24 months at a 3–6 monthly interval. Results: LBBP was successful in 29 of 33(87.9%) patients while all 37 of the remaining patients successfully underwent RVAP. Paced QRS duration was significantly narrower in the LBBP group compare to RVAP(110.75 ± 6.77 ms vs. 154.29 ± 6.96 ms, p = .000) at implantation, and the difference persisted during follow‐ups. Pacing thresholds (at implantation: 0.68 ± 0.22 V in the LBBP group and 0.73 ± 0.23 V in the RVAP group, p = .620) remained low and stable during follow‐ups. The cardiac function in the LBBP group remained stable during follow‐ups (LVEF%:55.08 ± 4.32 pre‐operation and 54.17 ± 4.34 at the end of follow‐up, p = .609), and better than RVAP group (LVEF%: 54.17 ± 4.34 vs. 50.14 ± 2.14, p = .005). Less HFH was observed in the LBBP group (2/29, 6.89%) compared to RVAP group (10/37, 27.03%). Conclusions: The present investigation demonstrates the safety and feasibility of LBBP that produces narrower paced QRS duration than RVAP. LBBP is associated with reduction in the occurrence of pacing‐induced left ventricular dysfunction and HFH compared to RVAP in patients requiring permanent pacemakers.